Supervisi Akademik Dalam Upaya Peningkatan Motivasi Guru Menyusun Perangkat Persiapan Pembelajaran - Maria Jacinta Doa (Ekspektasi: Jurnal Pendidikan Ekonomi, 2021)
This study aims to determine the effect of academic supervision on increasing teacher motivation in preparing learning preparation tools. The study was designed in 3 cycles, each of which consisted of planning, implementing, observing, reflecting and revising. The action taken is supervision followed by billing commitments and guidance. Data collection methods used were observation and interviews. Meanwhile, the data analysis method used is descriptive-comparative method. The results of the study, quantitatively, show an increase in teacher motivation in compiling syllabus and lesson plans from cycle 1, cycle 2 and cycle 3. In cycle 2, this is also the case in cycle 3. Based on the data on the results of the action from cycle to cycle, there appears to be a change or development of cycle 1 to cycle 2, and from cycle 2 to cycle 3. If in cycle 1, the number of teachers who submitted syllabus documents was 3 people or 37.5 percent, then in cycle 2, the number of teachers who had submitted documents increased by 1 person so that to 4 teachers or 50 percent. Furthermore, in cycle 3 the number of teachers who submitted documents increased by 2 people, so that the total number of teachers who had submitted documents up to cycle 3 became 6 people or 83.3 percent.